(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
The concentration of medium ingredients was optimized by applying statistical methods for production of citric acid by locally isolated Aspergillus niger PCSIR-06. Box-bhenken design and response surface methodology were applied for designing experiment and statistical analysis of results. The Box-bhenken design limited the number of experiments to fifty four for studying possible interaction between the six medium ingredients i.e., Sucrose, KH2PO4, NH4NO3, MgSO4, zinc and iron. The statistical method predicted maximum citric acid yield of 108.69 g/l with medium ingredients concentration Sucrose 149.92 g/l, KH2PO4 1.25 g/l, NH4NO3, 4.66 g/l, MgSO4 0.15 g/l, Zn 24.00 mg/l, Fe 0.21 mg/l. The verification run confirmed the predicted yield with the given concentration of medium ingredients. These studies successfully demonstrated the use of Box-Bhenken experimental design for the optimization of nutrient concentration for maximum yield of citric acid. Key words: Optimize; Medium; Citric acid; Box-bhenken design; Response surface methodology DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9606 BJSIR 2011; 46(4): 549-560